Synthesis and structural properties of ZnO doped nanoparticles prepared by hydrothermal method. Issue 186 (2nd January 2018) - Sharma, Neha; Kumar, Sanjay; Kumar, Jitender
ABSTRACT: The present study investigates the structural properties of pure and doped ZnO nanosized particles. The nanosized particles were synthesized by using hydrothermal process at room temperature. Nanoparticles have been characterized for its optical, structural properties using UV–VIS spectrophotometer and X-ray diffraction (XRD). XRD results show that the prepared samples have single phase and has hexagonal wurtzite structure. Further, the crystallite size of the ZnO nanoparticles have been determined using Scherrer, Williamson Hall method and size strain plot. The different chemical nature and different ionic radii are main effect, which shows different properties for the different dopant as compared to the host cation. Due to the different doping content, the crystallite size of nanoparticles found to be increased. The physical parameters such as strain-stress curve and energy values were calculated for all the reflected peaks of XRD data.